2005
DOI: 10.1007/s10456-005-9006-9
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in endometrial angiogenesis research

Abstract: This review summarises recent research into the mechanisms and regulation of endometrial angiogenesis. Understanding of when and by what mechanisms angiogenesis occurs during the menstrual cycle is limited, as is knowledge of how it is regulated. Significant endometrial endothelial cell proliferation occurs at all stages of the menstrual cycle in humans, unlike most animal models where a more precise spatial relationship exists between endothelial cell proliferation and circulating levels of oestrogen and prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
149
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(160 citation statements)
references
References 106 publications
7
149
0
4
Order By: Relevance
“…The human endometrium is a mucosa served by a microvascular blood supply that involves benign angiogenesis, which is under the control of ovarian steroids throughout reproductive life (14,15). In agreement with previous studies, we found AM and CLR to be expressed in all endometrial cell types (2).…”
Section: Discussionsupporting
confidence: 91%
“…The human endometrium is a mucosa served by a microvascular blood supply that involves benign angiogenesis, which is under the control of ovarian steroids throughout reproductive life (14,15). In agreement with previous studies, we found AM and CLR to be expressed in all endometrial cell types (2).…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with our hypothesis, Caballero-Campo et al (49) demonstrated using in vitro coculture experiments that both IL-8 mRNA expression and protein production were up-regulated in endometrial epithelial cells in the presence of a human blastocyst. In both menstruation and implantation, IL-8 production and infiltrated neutrophils may play a role in the angiogenesis for endometrial remodeling/regeneration, trophoblast invasion, and placentation, rather than prevention of the progression of infection (50). Further studies are needed to elucidate the role of P2RY14 in the various physiological processes of reproduction.…”
Section: Discussionmentioning
confidence: 99%
“…Copper has been shown to influence the bioactivity or production of a number of angiogenic factors including VEGF-A [5,8] and shares some of the pathways utilized by hypoxia to regulate VEGF-A expression [2,5] demonstrated that copper is having anti-tumor activity [9]. Copper is also required in hemoglobin synthesis and in the catalysis of metabolic oxidation [10].…”
Section: Discussionmentioning
confidence: 99%
“…The uterine endometrium is a dynamic tissue that undergoes regular cycles of growth and breakdown, and has long been recognized as one of the few adult tissues where significant angiogenesis occurs on a routine, physiological basis. Abnormal angiogenesis may contribute to several different endometrial-related pathologies including endometrial cancer, endometriosis, menorrhagia and breakthrough bleeding [2].…”
Section: Introductionmentioning
confidence: 99%